Pengembangan Media Pembelajaran Power Point Ispring Presenter Pada Materi Kosakata Bahasa Arab Peserta Didik Kelas V MI Tarbiyatul Athfal Lampung Timur - Guntur; Amiruddin; Nisaul Jamilah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2019)
Using media in language teaching has various weaknesses in terms of design, material aspects, and in terms of language. Based on this, the problem of this research "How is the development, feasibility, response of students to the power point learning media ispring the presenter on vocabulary material?" The research aims to: develop power point learning media, ispring presenters in vocabulary material and knowing the feasibility, effectiveness, and response of students to the ispring presenter's power point learning media. This research was conducted using the Research and Development (R & D) method which adopted the development of Borg & Gall. Instruments for data collection using questionnaires and interviews. Based on the results of this study, it was found that the development of the powerpoint ispring presenter included three main points, design, material and language. The feasibility of the validation results of the media expert team obtained an average percentage of 84%. The results of the validation of the material expert team obtained an average percentage of 89%. And the results of the validation of the linguist team gained an average percentage of 92%. The response of students to the attractiveness of learning media based on small-scale trials obtained an average score of 86.5% with interpretation criteria "Very Interesting", and in large-scale trials obtained an average score of 95.7% with interpretation criteria "Very Interesting". While the average score of a teacher as users is 86% with "Very Worth" interpretation criteria. Abstrak Penggunaan media pembelajaran yang selama ini digunakan memiliki berbagai kelemahan dilihat dari segi desain, materi, dan bahasa. Berdasarkan hal tersebut, penulis merumuskan masalah “Bagaimana pengembangan, kelayakan, respon peserta didik terhadap media pembelajaran power point ispring presenter pada materi kosakata?”. Adapun penelitian ini bertujuan untuk: mengembangkan media pembelajaran power point ispring presenter pada materi kosakata dan mengetahui kelayakan, keefektifan serta respon peserta didik terhadap media pembelajaran power point ispring presenter. Penelitian ini dilakukan dengan metode Research and Development (R&D) yang mengadopsi pengembangan dari Borg & Gall. Instrumen pengumpulan data menggunakan angket dan wawancara. Berdasarkan hasil penelitian ini diperoleh bahwa, pengembangan power point ispring presenter mencakup tiga hal pokok, yaitu desain, materi dan bahasa.. Kelayakan hasil validasi tim ahli media memperoleh presentase rata-rata sebesar 84%. Hasil validasi tim ahli materi memperoleh presentase rata-rata sebesar 89%. Dan hasil validasi tim ahli bahasa memperoleh presentase rata-rata sebesar 92%. Respon peserta didik terhadap kemenarikan media pembelajaran berdasarkan uji coba skala kecil diperoleh skor rata-rata 86,5% dengan kriteria interprestasi “Sangat Menarik”, dan pada uji coba skala besar diperoleh skor rata-rata 95,7% dengan kriteria interprestasi “Sangat Menarik. Sedangkan skor rata-rata pendidik sebagai pengguna adalah 86% dengan kriteria interprestasi “Sangat Layak”. Kata Kunci: Media Pembelajaran, Power Point Ispring Presenter, Kosakata